Access to Healthcare and Harm Reduction Services During the COVID-19 Pandemic for People Who Use Drugs. Issue 6 (December 2020) - Stowe, MJ; Calvey, Tanya; Scheibein, Florian; Arya, Sidharth; Saad, Noha Ahmed; Shirasaka, Tomohiro; Dannatt, Lisa; Ghosh, Abhishek; Yee, Anne; Ratta-apha, Woraphat; Vadivel, Ramyadarshni; Siste, Kristiana; et al.
Abstract : N/A: Globally, there are concerns about access to healthcare and harm reduction services for people who use drugs (PWUD) during the coronavirus disease 2019 (COVID-19) pandemic. Members from the Network of Early Career Professionals working in Addiction Medicine shared their experiences of providing treatment to PWUD during the COVID-19 pandemic. Drawing on these qualitative reports, we highlight the similarities and discrepancies in access to services for PWUD in 16 countries under COVID-10 restrictions. In most countries reported here, efforts have been made to ensure continued access to services, such as mobilising opioid agonist maintenance treatment and other essential medicines to patients. However, due to travel restrictions and limited telemedicine services, several Network of Early Career Professionals working in Addiction Medicine members from lower-resourced countries experienced challenges with providing care to their patients during periods of COVID-19 lock-down. The insights provided in this commentary illustrate how the COVID-19 lock-down restrictions have impacted access to services for PWUD.